Pengaruh Konten Instagram dan Electronic Word Of Mouth (EWOM) terhadap Minat Beli Konsumen Oishi Bento di Tanggerang Selatan - Satim Hamid; Arrofie Darmawan (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to determine the influence of Instagram content and electronic word of mouth (EWOM) on consumer purchase intention at Oishi Bento in South Tangerang, both partially and simultaneously. The population in this study was Oishi Bento consumers. The sampling technique used non-probability sampling, namely accidental sampling, and the respondents or sample was approximately 125 individuals. This is a quantitative study. This study uses two independent variables and one dependent variable. The dependent variable (Y) is consumer purchase intention. The independent variable (X) is Instagram content and electronic word of mouth (EWOM). The results of this study indicate: (1) There is a significant partial impact of Instagram content on consumer purchase intention; (2) There is a significant impact between electronic word of mouth (EWOM) on consumer purchase intention; (3) There is a significant positive simultaneous impact between Instagram content and electronic word of mouth (EWOM) on consumer purchase intention.